Migration Decision-Making and Its Key Dimensions. Issue 1 (September 2021) - Czaika, Mathias; Bijak, Jakub; Prike, Toby
Migration decisions are made in the context of personal needs and desires, and the individuals making these decisions face uncertain outcomes. Information about future opportunities is incomplete, and whether migration turns out to be a personal success or failure depends mostly on circumstances that are ex ante unknown and ex post not fully under the control of the individuals who migrate. This article elaborates on four dimensions of the complex process of migration decision-making: the formation of migration aspirations, the cognitive rules for searching and evaluating information about migratory options, the timing and planning horizons for preparing and realizing migratory decisions, and the locus of control and degree of agency in making migration decisions. We review the current state of evidence and identify opportunities for future empirical research that can help us to better understand these key dimensions of migration decision-making.